Low level direct interpolation for parametric curves (1998)
This article presents an algorithm for the direct interpolation of parametric planar curves C(u) with a CNC machine. It expresses parametric planar curves as sequences of machine tool axes discrete movements of BLU size. Therefore, the curve C(u) is directly approximated by the pulse trains, hence eliminating one source of the machining errors.